Microbiota of Palm Oil Mill Wastewater in Malaysia - Jeremiah David Bala,; Japareng Lalung,; Adel Ali Saeed Al-Gheethi,; Kaizar Hossain,; Norli Ismail, (Tropical Life Sciences Research, 2018)
This study was aimed at identifying indigenous microorganisms from palm oil mill effluent (POME) and to ascertain the microbial load. Isolation and identification of indigenous microorganisms was subjected to standard microbiological methods and sequencing of the 16S rRNA and 18S rRNA genes. Sequencing of the 16S rRNA and 18S rRNA genes for the microbial strains signifies that they were known as Micrococcus luteus 101PB, Stenotrophomonas maltophilia 102PB, Bacillus cereus 103PB, Providencia vermicola 104PB, Klebsiella pneumoniae 105PB, Bacillus subtilis 106PB, Aspergillus fumigatus 107PF, Aspergillus nomius 108PF, Aspergillus niger 109PF and Meyerozyma guilliermondii 110PF. Results revealed that the population of total heterotrophic bacteria (THB) ranged from 9.5 × 105 – 7.9 × 106 cfu/mL. The total heterotrophic fungi (THF) ranged from 2.1 × 104 – 6.4 × 104 cfu/mL. Total viable heterotrophic indigenous microbial population on CMC agar ranged from 8.2 x 105 – 9.1 × 106 cfu/mL and 1.4 × 103 – 3.4 × 103 cfu/mL for bacteria and fungi respectively. The microbial population of oil degrading bacteria (ODB) ranged from 6.4 × 105 – 4.8 × 106 cfu/mL and the oil degrading fungi (ODF) ranged from 2.8 × 103 – 4.7 × 104 cfu/mL. The findings revealed that microorganisms flourish well in POME. Therefore, this denotes that isolating native microorganisms from POME is imperative for effectual bioremediation, biotreatment and biodegradation of industrial wastewaters. Kajian ini bertujuan untuk mengenal pasti mikroorganisma asli daripada efluen kilang minyak sawit (POME) dan untuk menentukan beban mikrob. Pengasingan dan pengenalpastian mikroorganisma asli tertakluk kepada kaedah piawai mikrobiologi dan penjujukan gen 16S rRNA dan 18S rRNA. Penjujukan daripada gen16S rRNA dan 18S rRNA untuk strain mikrob menunjukkan bahawa mereka dikenali sebagai Micrococcus luteus 101PB, Stenotrophomonas maltophilia 102PB, Bacillus cereus 103PB, Providencia vermicola 104PB, Klebsiella pneumonia 105PB, Bacillus subtilis 106PB, Aspergillus fumigates 107PF, Aspergillus nomius 108PF, Aspergillus niger 109PF dan Meyerozyma guilliermondii 110PF. Keputusan menunjukkan bahawa jumlah populasi bakteria heterotropik (THB) berkisar antara 9.5 × 105 – 7.9 × 106 cfu/mL. Jumlah heterotopic fungi (THF) berkisar antara 2.1 × 104 – 6.4 × 104 cfu/mL. Jumlah populasi mikrob asli heterotropik pada medium agar CMC masing-masing berkisar antara 8.2 x 105 – 9.1 × 106 cfu/mL (bakteria) dan 1.4 × 103 – 3.4 × 103 cfu/mL (fungi). Penemuan mendapati bahawa mikroorganisma berkembang dengan baik di dalam efluen kilang minyak kelapa sawit (POME). Oleh itu, ini menunjukkan bahawa pengasingan mikroorganisma asli dari efluen kilang minyak sawit (POME) adalah penting untuk bioremediasi, rawatan bio dan biodegradasi sisa industri yang berkesan.